PEMBINAAN ANAK JALANAN MELALUI POLA ASUH DI RUMAH SINGGAH DAN BELAJAR (RSB) DIPONEGORO SLEMAN YOGYAKARTA - Ageng Widodo; Siswanto Siswanto (UIN Sunan Kalijaga Yogyakarta, 2019)
The pattern of asuh was an image of that is worn parents to them should be responsible for ( has the care of, keeping or educate ) anak. Sedangkan the pattern of a good foster is of many patterns asuh who capable of forming the personality of the son of characterless, to become a better place, and make certain things to parents who do not .But as for foster the complexities of the patterns that is applied by the house of turns aside and spreads his and learn ( RSB) Diponegoro is of many patterns asuh that would lead to a the formation of the fulfillment of education, the health of its people, of developing kind of confidence , children welfare and .As a result of this, when all other needs met then the welfare of kids is going to come upon them an overwhelming.Keywords: Foster pattern , Children, RSB Diponegoro